Development of a comprehensive frailty test battery including physical, socio-psychological and cognitive domains for patients with cardiovascular disease. (29th July 2021) - Marinus, N; Vigorito, C; Giallauria, F; Dendale, P; Meesen, R; Scherrenberg, M; Spildooren, J; Hansen, D
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Frailty is an age-related decline in physical, socio-psychological and cognitive function resulting in extreme vulnerability to stressors. In patients with cardiovascular disease (CVD) it remains to be elucidated which tests to select to detect/establish frailty in a comprehensive, valid and feasible manner. Purpose: 1) To compare the frailty prevalence rates using Fried vs. the more comprehensive Vigorito criteria in CVD patients; 2) To establish which tests, from the physical, socio-psychological and cognitive domains, should be selected to be able to detect frailty in patients with CVD; 3) To establish a total score that may represent a valid measurement of frailty severity, and 4) To examine the association of frailty with long-term clinical outcomes. Methods: Patients (n = 133, mean age 78 ± 7 years) hospitalised for coronary revascularisation or heart failure (HF) were examined by the Fried and Vigorito criteria (Mini Nutritional Assessment (MNA), Katz-scale, 4.6m gait speed, timed up-and-go test (TUG), handgrip strength, Mini Mental State Examination (MMSE), Geriatric Depression Scale (GDS-15), number of medications). Additionally, physical activity, time spent sitting, knee extension and hip flexor muscle strength, timed chair-stand test and fear of falling were measured. Multivariate regression and sensitivity/specificity analyses were performed to assess which tests to adopt to detect frailty in CVD patients. Moreover, hospitalisations and mortality, up to six months after the initial hospital admission were examined. Results: Any level of frailty was detected in 44% of the patients by the Vigorito criteria and in 65% of the patients by the Fried criteria. However, frailty state may have been overestimated by Fried score as 20% of patients classified as non-frail by Vigorito, were pre-frail by Fried. Furthermore, 10% vs. 38%, respectively, were classified as moderate-frail (by Vigorito) vs. frail (by Fried). Frailty could best be detected (at the earliest stage) by a score from: sex, MNA, Katz-scale, TUG, handgrip strength, MMSE, GDS-15, total number of medications (cut-off score ≥5.56: sensitivity: 1.0, specificity: 0.54, correlation with Vigorito score: r = 0.98, p < 0.001). During the six-month follow-up period, 39% of the patients were readmitted to the hospital (56% of these hospitalisations were attributed to the HF patients) and 7% of the subjects died (89% of them were HF patients). Frailty and specific markers of frailty were significantly associated with mortality and six-month general, urgent, orthopaedic and cardiovascular hospitalisations. Conclusions: To detect frailty in patients with CVD, even at an earliest stage, sex, MNA, Katz-scale, TUG, handgrip strength, MMSE, GDS-15 and total number of medications play a key role, assessed by a new time- and cost-efficient test battery for frailty.